Marketing plan and employee competencies on performance In The Marketing Department Of The Indonesian Tobacco Company, Tbk - Agus Iwhan Ariftian Zuhdi; Arif Hidayat (Jurnal Mantik, 2024)
Restrictions and prohibitions on promotions, advertising and even sponsorship as a means of marketing tobacco-based products are a challenge for tobacco-based producing companies. The company strives to increase excellence in preparing marketing plans and competent human resources to achieve company performance. The aim of this research is to examine the influence of marketing planning and employee competency on company performance. This descriptive research took a sampling of marketing employees at PT. Indonesian Tobacco, tbk using total population study techniques, and data collected through questionnaires and company performance documents. The results of the structural equation model (SEM) analysis show that the predictor model construct is quite good; the results of the hypothesis test show a value of t= 2.030 at p=0.043 (p<0.05) which means that the marketing plan has a significant effect on company performance; and the t value = 5.615 at p = 0.000 (p <0.05) proves that employee competency has a significant effect on company performance. So it can be concluded that marketing plans and employee competency have a significant effect on company performance, and marketing plan variables and employee competency can be used as predictive tools to measure the level of success or performance of companies that experience restrictions and prohibitions on marketing activities